(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
Recently, radiation pollution has become a serious problem in which microwave radiation leads to various issues, such as health problems in humans. To address this issue, anti-microwave organic cement bricks were designed and fabricated. This study investigates the effectiveness of biomass used as absorbent materials when combined with cement to eliminate microwave radiation. Biomass materials that were indicated in this study were fine sawdust, rice husk, and coconut husk. The anti-microwave organic cement brick was designed in size of 216 mm length x 103 mm width x 65 mm thickness which is almost the same as commercial sand brick, 200 mm length x 100 mm width x 60 mm thickness. CST Microwave Studio Suite software was used to obtain the simulation results of the designed absorber. The free-space arch reflectivity measurement method was used to investigate the absorption performance of the designed anti-microwave organic cement brick in the frequency range of 1 to 12 GHz. This study evaluates the absorption performance of designed anti-microwave organic cement brick using commercial sand brick as benchmarks. The result shows that the organic cement brick which uses 20 % fine sawdust, 20 % rice husk, and 20 % coconut husk has the potential as an anti-microwave material that can reach a higher absorption performance of up to –44.36 dB compared to the commercial sand brick which only reaches absorption performance at -12.74 dB.